A-13 Demographic Differences in Performance Validity Test Failures. (28th August 2020) - Braun, S; Fountain-Zaragoza, S; Halliday, C; Horner, M
Abstract: Objective: The present study aimed to investigate demographic differences in performance validity test (PVT) failure in a Veteran sample. Method: Data were extracted retrospectively from neuropsychological evaluations at a southeastern Veterans Affairs (VA) Medical Center. Only male Veterans who were either European American/White (EA) or African American/Black (AA), and for whom complete data were available were included in the study (N = 1271). We investigated whether performance on two frequently used PVTs, the Test of Memory Malingering (TOMM) and the Medical Symptom Validity Test (MSVT), significantly differed by age, education, race, and VA service connection using separate logistic regressions. Results: Veterans with younger age, less education, and VA service-connected disability were significantly more likely to fail both PVTs. Race was not a significant predictor of MSVT failure, but AA patients were significantly more likely than EA patients to fail the TOMM. For all significant demographic predictors in the models, effects were small. In a subsample of patients who were given both PVTs (n = 467), the pattern of differences based on race remained; 46% of AA patients and 36% of EA patients failed the TOMM, while 44% of AA patients and 43% of EA patients failed the MSVT. Conclusions: Performance on the TOMM and MSVT systematically differed based on demographics. Results were not consistent across PVTs, with performance on the TOMM differing between EA and AA patients, but performance on the MSVT did not differ by race. These results suggest that demographic factors may play a small but measurable role in performance on specific PVTs.